Bilateral Neonatal Suppurative Parotitis in a Brazilian Preterm Infant: A Case Report - Guedes, Sarah Cavalcanti; Cabral, Luiza Lyra; Arcoverde, Maria Victória Azevêdo de Araújo; Van-dunem, Aurora Nateta de Aleluia David; Alves, João Guilherme (Brazilian Journal of Case Reports, 2026)
Neonatal suppurative parotitis is a rare bacterial infection of the salivary glands in newborns, often associated with risk factors such as prematurity, dehydration, and retrograde contamination from the oral cavity. To date, fewer than 100 cases of neonatal suppurative parotitis have been published worldwide. While uncommon, it requires prompt clinical recognition to ensure a favorable prognosis and prevent systemic complications. This report details a case of bilateral neonatal suppurative parotitis in a 10-day-old preterm female neonate (34 weeks of gestation). The patient presented with fever, irritability, and bilateral pre-auricular swelling with purulent drainage from Stensen’s duct. Ultrasound confirmed the diagnosis, and cultures grew methicillin-sensitive Staphylococcus aureus (MSSA). The infant was successfully treated with a 10-day course of intravenous antibiotics (cefepime and clindamycin), resulting in complete resolution of symptoms. In conclusion, this represents a rare case of bilateral neonatal suppurative parotitis. Early diagnosis through clinical examination and imaging, followed by targeted antibiotic therapy, is essential for a full recovery and the prevention of complications like abscess formation or sepsis.